2003
DOI: 10.1001/jama.289.23.3095
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Major Depressive Disorder

Abstract: LTHOUGH COMMUNITY SURveys of mental disorders have been conducted in the United States since the end of World War II, 1-3 it was not until the early 1980s that fully structured lay interviews were developed to diagnose specific mental disorders. The first such instrument was the Diagnostic Interview Schedule (DIS), 4 which was developed for use in the Epidemiologic Catchment Area (ECA) study 5 to estimate the general population prevalence of mental disorders by Diagnostic and Statistical Manual of Mental Disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

96
2,129
19
42

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 7,098 publications
(2,286 citation statements)
references
References 60 publications
96
2,129
19
42
Order By: Relevance
“…The effectiveness of MDD treatment in relation to functional outcomes is potentially confounded by the bidirectional relationship of depressive symptoms and functional impairment, as well as by premorbid functioning, which may not be accounted for when assessing the reduction in functional impairment (McKnight & Kashdan, 2009). The National Comorbidity Survey Replication found that 96.9% of patients with MDD for at least 12 months also suffered from functional impairment (in at least one area) associated with their depression, with 19.1% of patients reporting their impairment as “very severe” (Kessler et al., 2003). These respondents also reported being unable to work or fulfill daily activities for an average of 35.2 days in the past year of their MDD (Kessler et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of MDD treatment in relation to functional outcomes is potentially confounded by the bidirectional relationship of depressive symptoms and functional impairment, as well as by premorbid functioning, which may not be accounted for when assessing the reduction in functional impairment (McKnight & Kashdan, 2009). The National Comorbidity Survey Replication found that 96.9% of patients with MDD for at least 12 months also suffered from functional impairment (in at least one area) associated with their depression, with 19.1% of patients reporting their impairment as “very severe” (Kessler et al., 2003). These respondents also reported being unable to work or fulfill daily activities for an average of 35.2 days in the past year of their MDD (Kessler et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The National Comorbidity Survey Replication found that 96.9% of patients with MDD for at least 12 months also suffered from functional impairment (in at least one area) associated with their depression, with 19.1% of patients reporting their impairment as “very severe” (Kessler et al., 2003). These respondents also reported being unable to work or fulfill daily activities for an average of 35.2 days in the past year of their MDD (Kessler et al., 2003). Understanding the relationship between MDD and functionality is important, especially considering the cost of lost work productivity due to absenteeism and presenteeism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a lifetime prevalence of around 16.2% (Kessler et al, 2003) and recurrence rates between 35% in the general population and 85% in specialized mental health facilities (Hardeveld, Spijker, De Graaf, Nolen, & Beekman, 2010), affective disorders (mainly major depression) belong to the second most frequent group of disorders (Wittchen & Jacobi, 2005). Therefore, early intervention in individuals with mild depressive symptoms—and prevention of major depressive disorder before it emerges—is of crucial importance for public health.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence‐based treatments, about 20% of all depressed patients develop a chronic course (Kessler et al., 2003), typically defined as a period of 2 years or longer of depressive symptoms (DSM‐IV‐TR, 2000). Chronic depression not only affects the personal life of a patient, but is also associated with high costs for society in terms of health care costs and workplace losses (Pincus, 2001).…”
Section: Introductionmentioning
confidence: 99%